Simultaneous Vestibular Schwannoma Resection and Cochlear Implantation Using Electrically Evoked Auditory Brainstem Response Audiometry for Decision-making. Issue 9 (October 2020) - Dahm, Valerie; Auinger, Alice B.; Honeder, Clemens; Riss, Dominik; Landegger, Lukas D.; Moser, Gerhard; Matula, Christian; Arnoldner, Christoph
Abstract : Objective: The aim of the study was to evaluate the predictive value regarding postoperative hearing benefit of electrically evoked auditory brainstem response audiometry in sporadic vestibular schwannoma patients undergoing simultaneous tumor resection and cochlear implantation. Design: Patients were included in a prospective study conducted between October 2016 and January 2019. Setting: The study was conducted at a tertiary care center. Participants: Subjects with unilateral sporadic vestibular schwannoma were screened for study participation. Patients underwent translabyrinthine vestibular schwannoma resection and cochlear implantation simultaneously. Intervention: Electrically evoked brainstem response audiometry was performed during surgery before and after tumor removal using an intracochlear test electrode to objectively evaluate nerve conduction. Main Outcome Measure: Electrically evoked brainstem response audiometry results were correlated with postoperative sound field audiometry, word recognition tests, and speech reception thresholds. Quality of life was assessed before and 12 months after translabyrinthine tumor removal and cochlear implantation. Results: Five patients, three male and two female, were included in the study and followed for at least 1 year after implantation. Three of the five patients are daily cochlear implant users with open set speech recognition. Two individuals with negative intraoperative electrically evoked auditory brainstem response results showed no auditory perception with cochlear implant. Conclusions: Simultaneous translabyrinthine vestibular schwannoma resection and cochlear implantation with intraoperative electrically evoked auditory brainstem response measurements is a feasible and promising option for sporadic vestibular schwannoma patients. Preservation of electrically evoked auditory brainstem responses seems to predict good subsequent hearing outcomes.